Lactate Ameliorates Kainic Acid-Induced Neuroinflammation and Cognitive Impairment via the Chemokine Signaling Pathway in Mice - Chu X; Ge Y; Geng C; Cao P; Wei P; Fu B; Deng Z; Li Y; Zhao G (Journal of Inflammation Research)
Xiaoqi Chu,1,2,* Yusong Ge,3,* Chao Geng,1,2 Peipei Cao,1,2 Penghu Wei,2 Bin Fu,2 Zihao Deng,4 Yuhao Li,5,6 Guoguang Zhao2,7 1Optometry Institute, School of Medicine Nankai University, Tianjin, People’s Republic of China; 2Department of Neurosurgery, Xuanwu Hospital Capital Medical University, Beijing Municipal Geriatric Medical Research Center, Beijing, People’s Republic of China; 3Department of Neurology, The Second Hospital of Dalian Medical University, Dalian, People’s Republic of China; 4Cancer Center, Capital Medical University, Beijing, People’s Republic of China; 5Central Laboratory, Xuanwu Hospital Capital Medical University, Beijing Municipal Geriatric Medical Research Center, Beijing, People’s Republic of China; 6Department of Pathology, School of Medicine Nankai University, Tianjin, People’s Republic of China; 7National Medical Center for Neurological Diseases, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guoguang Zhao, Department of Neurosurgery, Xuanwu Hospital Capital Medical University, Beijing Municipal Geriatric Medical Research Center, Beijing, People’s Republic of China, Email ggzhao@vip.sina.com Yuhao Li, Central Laboratory, Xuanwu Hospital Capital Medical University, Beijing Municipal Geriatric Medical Research Center, Beijing, People’s Republic of China, Email liyuhao@xwhosp.orgPurpose: Lactate, previously considered a metabolic waste product, has been shown to have neuroprotective potential. This study aims to investigate the impact of lactate intervention and its underlying mechanisms on epilepsy.Methods: HT22 cells were stimulated with glutamate to construct an excitotoxicity cell model. An acute epilepsy model was established in mice by kainic acid induction. The neuronal damage, microglial activation, inflammatory responses, and functional changes were determined by TUNEL assays, immunohistochemistry, quantitative real-time polymerase chain reaction and behavioral tests. The differentially gene expression and functional enrichment were analyzed with RNA sequencing.Results: The in vitro lactate intervention reduced the number of apoptotic cells, the release of inflammatory factors, and the expression of vesicular glutamate transporter 1. In mice with acute epilepsy, lactate treatment mitigated neuronal damage, microglial activation, and inflammatory responses in the hippocampus and ameliorated anxiety-like behavior and cognitive impairment.Conclusion: Lactate exerts therapeutic effects on epilepsy through the chemokine signaling pathway. The neuroinflammation is an important contributor to cognitive impairment. Targeting inflammatory pathways is a promising strategy for improving the prognosis of epilepsy. Keywords: lactate, neuroinflammation, cognitive impairment, neuronal damage, chemokine, epilepsy